No safe place for war survivors: War memory, event exposure, and migrants' psychological trauma - Ahmad, Muhammad Sohail; Bukhari, Zainab; Khan, Sundas; Ashraf, Imran; Kanwal, Asma (Frontiers in Psychiatry, 2023)
The research explores the concept of reenactment of war trauma (known and unknown) that seems unfamiliar to the readers, albeit opening up new discourses of understanding and empathy through the lens of Cathy Caruth’s trauma theory by focusing on the novel A Land of Permanent Goodbyes by Atia Abawi. War fiction, such as Abawi’s novel, highlights the concept of psychological trauma as a double wound (known as “outsiders”, and not known as “insiders”) through the textual analysis and characterization of characters by presenting their haunting past, present lives, and loss concerning traumatic events. The research also recounts what the trauma of not knowing means to war-torn survivors by focusing on ‘trauma as double wounds’ and three segments: cause, effects, and recuperation. Finally, the study finds a new paradigm and shows trauma as a healer instead of merely a wound.